The role of fluorine in the concentration and transport of lithophile trace elements in felsic magmas: Insights from the Gawler Range Volcanics, South Australia - Agangi, Andrea; Kamenetsky, V.; McPhie, J. (Elsevier Science BV, 2010)
Rhyolites of the Mesoproterozoic Gawler Range Volcanics (GRV) of South Australia are characterised by high concentrations of some trace elements (REE, Y, HFSE, Rb and F, in particular). Whole rock geochemical data suggest that these elements were incompatible during magma crystallisation. Accessory minerals (fluorite, zircon, REE-F-carbonate, Ti oxide, apatite, and titanite) can account for most of the trace element content of the rocks. These minerals occur in vesicles, micromiaroles, lithophysal vugs and in interstices between major mineral phases (quartz and feldspar as both phenocrysts and groundmass). Such textural evidence indicates that accessory minerals crystallised late in the history of the magma and that they were deposited from a volatile-rich (fluid) phase. These features are explained by the following sequence of events: 1) F dissolved in the magma lowered the crystallisation temperature of accessory minerals, causing trace elements (REE, Y, and HFSE) to behave as incompatible elements. 2) Protracted crystallisation of major mineral phases (quartz, feldspar, and oxides) formed a volatile- and trace element-enriched residual liquid. 3) A volatile element (H2O, F, and CO2)-rich phase (late-stage magmatic fluid) evolved from the magma. High concentration of fluorine and other complexing agents in this phase allowed trace elements to be transported in solution. 4) Accessory minerals crystallised from such a phase in vesicles, micromiaroles and interstices between the major mineral phases. © 2010 Elsevier B.V.